SETTLING INTERNAL STRENGTHS AND EXTERNAL DEPENDENCIES: A CONCEPTUAL FRAMEWORK INTEGRATING RDT AND RBV THEORIES FOR ORGANIZATIONAL SURVIVAL - Kui, Daniel Ong Kim; Widjaja, Anton Wachidin; Pramono, Rudy (Universitas Pelita Harapan, 2024)
The purpose of this study is to explore the integration of two mainstream theories of strategic management rooted in resource Dependency Theory (RDT) and Resource-Based View (RBV) in utilizing the internal strengths and external dependencies of companies. This study will explore the area of theory integration by using a literature review method that involves the collection, analysis and synthesis of influential publications on both theories, semi-systematic literature review is carried out with narrative analysis techniques. The results of the study provide a conceptual framework in understanding organizational strategy and to gain stability in managing the main sources of competitive advantage and dependency of the organization. Studies of how organizations are leveraging their internal strengths, and external dependencies can reveal improvement trends and under-explored areas in strategic management research. The implications of exploring the integration of these two key perspectives will enhance the prospect of using both theories together in strategic planning, organizational behavior and decision-making, and serve as an integration view for managers to engage in process utilization. Internal forces and external dependencies are rooted in two mainstream theories: Resource Dependency Theory (RDT) and Resource Based View (RBV). This study explores the area of integration of these theories using a literature review method that involves the collection, analysis, and synthesis of existing influential publications from both theories. The implications of this research provide a conceptual framework in understanding organizational strategy and to gain stability in managing the main sources of competitive advantage and dependency of the organization